MAKNA LIRIK LAGU “INOCHI NI KIRAWARETE IRU” KARYA KANZAKI IORI - Anak Agung Putu Wahyu Adiarta; Anak Agung Ayu Dian Andriyani; Ni Luh Gede Meilantari (Program Studi Sastra Jepang Fakultas Bahasa Asing Unmas Denpasar, 2023)
This study aims to discuss the analysis of meaning in the lyrics of the song Inochi ni Kirawarete Iru with the research subject being the researcher himself. The object of research is the lyrics of a song by Kanzaki Iori entitled Inochi ni Kirawarete Iru. The method used in collecting data in this research is the method of discourse analysis/observation and focused discussion with the data source of the song lyrics of Inochi ni Kirawarete Iru. The data were analyzed with a qualitative descriptive semiotic approach, which resulted in data in the form of sentences or words contained in the lyrics of the song Inochi ni Kirawarete iru. The results of this study are the meaning of the lyrics of a song by Kanzaki Iori entitled Inochi ni Kirawarete iru about the bitterness of life that is felt by someone with feelings that require choosing in life.